Numerical study of viscoplastic flow in a T-bifurcation: Identification of stagnant regions - Inacio G.R.* (2019)
© 2019 Assoc. Brasiliera de Eng. Quimica / Braz. Soc. Chem. Eng.. All rights reserved.- Identification of stagnant regions of viscoplastic fluid flows in production lines and equipment is of paramount importance owing to potential material degradation and process contamination. The present work introduces an assessment strategy to identify, classify and quantify unyielded regions with the objective of optimizing the flow conditions with the purpose of minimizing stagnant regions. Flow of Carbopol® 980 in a T-bifurcation channel is adopted to illustrate the procedure. The rheological behavior of Carbopol® 980 was simulated using the Herschel-Bulkley viscoplastic model regularized by Papanastasiou’s exponential approach. The analysis shows that three distinct types of stagnant unyielded regions take place in the bifurcation channel depending upon the Reynolds condition. Furthermore, the rheological characteristics of the fluid indicate the existence of an ideal Reynolds condition which allows the smallest flow stagnant area at the bifurcation zone.